2019
DOI: 10.1155/2019/1439141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depth of Electroacupuncture on the IPSS of Patients with Benign Prostatic Hyperplasia

Abstract: is study aimed to evaluate the efficacy of electroacupuncture (EA) on Ciliao (BL 32) and Zhongliao (BL 33) acupoints at different depths for the treatment of benign prostatic hyperplasia (BPH) through a single-blind randomized controlled trial. All 120 patients diagnosed with BPH were randomly allocated to an experimental group (deep insertion group, DI group, n � 60) and control group (shallow insertion group, SI group, n � 60) 3 times a week for 4 weeks. e observed results included the International Prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
2
Order By: Relevance
“…Quanto aos PtA utilizados na eletroacupuntura, a maioria incluiu pelo menos um ponto referente ao meridiano da bexiga (20,25,29) , com destaque para o PtA B32 (Ciliao) (20,29) . Estudos recentes identificaram resultados significativos para o tratamento de sintomas da HPB em homens (49) e de sintomas de bexiga hiperativa (BH) em ratos a partir da estimulação do PtA B32 (50) . Sabe-se que o PtA B32 é um dos quatro pontos localizados nos quatro forames sacrais, sendo considerado o mais importante por possuir indicações amplas (disfunções miccionais, dismenorreia, dor lombar e ciática e infertilidade) e ser um dos pontos que produz maior efeito tonificante do Rim e Essência (51) .…”
Section: Discussionunclassified
“…Quanto aos PtA utilizados na eletroacupuntura, a maioria incluiu pelo menos um ponto referente ao meridiano da bexiga (20,25,29) , com destaque para o PtA B32 (Ciliao) (20,29) . Estudos recentes identificaram resultados significativos para o tratamento de sintomas da HPB em homens (49) e de sintomas de bexiga hiperativa (BH) em ratos a partir da estimulação do PtA B32 (50) . Sabe-se que o PtA B32 é um dos quatro pontos localizados nos quatro forames sacrais, sendo considerado o mais importante por possuir indicações amplas (disfunções miccionais, dismenorreia, dor lombar e ciática e infertilidade) e ser um dos pontos que produz maior efeito tonificante do Rim e Essência (51) .…”
Section: Discussionunclassified
“…(Ciliao) (20,29) . Recent studies have identified significant results for the treatment of BPH symptoms in men (49) and overactive bladder (OB) symptoms in rats based on AcPt B32 stimulation (50) . It is known that AcPt B32 is one of the four points located in the four sacral foramina, being considered the most important because it has broad indications (voiding dysfunctions, dysmenorrhea, low back pain and sciatica and infertility) and is one of the points that produces the greatest tonifying effect of the Kidney and Essence (51) .…”
Section: Discussionmentioning
confidence: 99%
“…The control intervention groups (control group) included various sham acupuncture treatments including different needle depth, other remedies, and other acupoints. Details are summarized in the following table [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the results showed that the treatment group EA had a statistically significant therapeutic effect when compared with the sham acupuncture group. Yuan et al [27] compared differences between the efficacy of deep and shallow acupuncture, and also noted the presence or absence of a radiating sensation to the anterior genital area. It was reported that the deep needling group had statistically significantly more efficacy in half of the outcome indices compared with shallow needling [27].…”
Section: Sham Acupuncturementioning
confidence: 99%